2006
DOI: 10.2337/dc05-1887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glycemic Control on Survival of Diabetic Patients on Chronic Regular Hemodialysis

Abstract: OBJECTIVE—To investigate the impact of glycemic control during regular hemodialysis on the survival of diabetic patients with chronic kidney disease (CKD) in a longitudinal observational study. RESEARCH DESIGN AND METHODS—A total of 114 diabetic CKD patients on hemodialysis at Inoue Hospital (Suita, Japan) were surveyed from May 1995 to December 2002 (survey period 45.5 ± 29.3 [means ± SD] months). All subjects were categorized into three groups by mean HbA1c (A1C) level during the 3-month perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 17 publications
5
112
4
5
Order By: Relevance
“…Although these trials excluded patients on hemodialysis, it has been argued that better glycemic control is key toward preventing DM‐related complications in this population 3, 7, 8, 9. In fact, surprisingly few studies have investigated the association between HbA 1c and clinical outcomes in the dialysis population 3, 10, 11, 12, 13, 14, 15, 16. Most of these studies focused only on all‐cause mortality as the outcome and were limited by small sample size and correspondingly low statistical power 11, 12, 13, 15…”
Section: Introductionmentioning
confidence: 99%
“…Although these trials excluded patients on hemodialysis, it has been argued that better glycemic control is key toward preventing DM‐related complications in this population 3, 7, 8, 9. In fact, surprisingly few studies have investigated the association between HbA 1c and clinical outcomes in the dialysis population 3, 10, 11, 12, 13, 14, 15, 16. Most of these studies focused only on all‐cause mortality as the outcome and were limited by small sample size and correspondingly low statistical power 11, 12, 13, 15…”
Section: Introductionmentioning
confidence: 99%
“…In addition, limited studies showed an association of poor glycemic control with poor survival on chronic dialysis (8,9). However, several studies showed no correlation…”
Section: In Diabetic Patients Glycemic Control Has An Essential Rolementioning
confidence: 99%
“…31 Although in the population with no CKD a strict control of diabetes is associated with a reduction in chronic complications 32 , in the HD population, a stricter control of glycemia protected patients against death due to infectious processes, but not against those due to cardiovascular events. 33 Dyslipidemia in CKD and its association with CVD has been extensively discussed, and several mechanisms relating that abnormality to systemic inflammation and to atherosclerosis triggers have been shown. 34 In patients with non-dialytic CKD, the reduction in cholesterol levels with statins has been associated with a reduction in coronary events, but had no influence on cardiovascular mortality.…”
Section: Clinical Management Of Cvd In Ckdmentioning
confidence: 99%